Pengembangan Media Praktikum Percobaan Hukum Oersted Pada Materi Elektromagnetik - Sri Wulan Dari; Okta Selviana; M. Jhoni (Departement of Mathematics Education, 2024)
This research focuses on developing practical media in the form of practical tools for Oersted's Law on electromagnetic materials. The reason for this research is taken from a problem that usually occurs in schools where the facilities and infrastructure are inadequate for carrying out practicums so that it is difficult to explain the concept of electronic materials. This research aims to develop a set of learning media in the form of practical tools about Oersted's Law in electromagnetic material, more precisely material about electromagnetic induction. With this media, students are expected to more easily understand the concept of electromagnetic induction. The practicum media development stages include (1) data collection (2) product design (3) design verification (4) design modification (5) product testing (6) product modification (7) prototype production (8) mass production. The tools and materials used are a compass, battery, wire, nails and wooden planks which are arranged and combined